The International Criminal Court: justice in ivory tower? - Ismail, Shahrul Mizan (HELP University College, 2006)
The repression, pursuant to the principles of the Nuremberg judgment, of international crimes against peace and humanity, which the General Assembly of the United Nations confirmed by its resolution of 11 December 1946, can only be ensured by the establishment of an International Criminal Court. This would avoid any future recurrence of the criticism often leveled against the International Military Tribunal for the trial of major war criminals, that it was an ad hoc court, which only imperfectly represented the international community. -Memorandum submitted to the United Nations Committee on the Progressive Development of International Law and its Codification by Henri Donnedieu de Vabres, representative of France and former Judge of the International Mililary Tribunal at Nuremberg, 15 May 1947.